2012
DOI: 10.5897/ijps11.507
|View full text |Cite
|
Sign up to set email alerts
|

NMR and NBO calculation of benzimidazoles and pyrimidines: Nano physical parameters investigation

Abstract: Six theoretical methods were used for the calculation of physical parameters for derivatives of pyrimidines and benzimidazols. We used Gaussian 98 at NMR and NBO calculations by using HF method with 6-31G, 6-31G* and 6-31+G basis set and B3LYP, BLYP and B3PW91 methods with 6-31G basis set. Chemical shift was drawn curve for all of the atoms in each molecule. The thermo chemical parameters including thermal energy(ΔΕ), atomic charges, chemical shift anisotropy(δ), asymmetry parameter(η), chemical shift anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…We found that the IHB energy is 6.23 kcal/mol for S 0 , and 6.13 kcal/mol for S 1 . These values are in agreement with the reported values in similar compounds harboring IHB (Muhammad et al, 2010; Abdel Ghani and Mansour, 2012; Monajjemi, 2012; Carreño et al, 2016; Yankova and Radev, 2016), and support the stability of this interaction (Sosa et al, 2002). In this sense, the experimental UV-vis results (see Table S2) were corroborated by computational methods (see and Figure S9).…”
Section: Resultssupporting
confidence: 91%
“…We found that the IHB energy is 6.23 kcal/mol for S 0 , and 6.13 kcal/mol for S 1 . These values are in agreement with the reported values in similar compounds harboring IHB (Muhammad et al, 2010; Abdel Ghani and Mansour, 2012; Monajjemi, 2012; Carreño et al, 2016; Yankova and Radev, 2016), and support the stability of this interaction (Sosa et al, 2002). In this sense, the experimental UV-vis results (see Table S2) were corroborated by computational methods (see and Figure S9).…”
Section: Resultssupporting
confidence: 91%
“…We also studied electronic structures of NAA and MAA using Natural Bond Orbital (NBO) analysis at the same levels that were mentioned above in gas phase. A full NBO analysis is obtained in Gaussian 98 [27][28][29] . The main listing of NBOs, displaying the form and occupancy of the complete set of NBOs that span the input AO space and for each orbital gives the type of orbital and the occupancy [29][30][31] .…”
Section: Methodsmentioning
confidence: 99%